Methods to appraise available evidence and adequacy of data from a systematic literature review to conduct a robust network meta-analysis of treatment options for patients with hospital-acquired or ventilator-associated bacterial pneumonia. - Laura Puzniak; Ryan Dillon; Thomas Lodise (PLoS ONE)
We aimed to determine if available evidence from a previously conducted systematic literature review was sufficient to conduct a robust network meta-analysis (NMA) using the International Society for Pharmacoeconomics and Outcomes Research Good Practice Task Force NMA study questionnaire to evaluate suitability, relevance, and credibility of available randomized-controlled trials (RCT) of antibacterial therapies for treatment of patients with hospital-acquired or ventilator-associated bacterial pneumonia (HABP/VABP). We assessed feasibility and reliability of an NMA for a connected network of RCTs, and then relevance and credibility of the connected network for informing decision-making. This previously conducted systematic literature review using Cochrane dual-reviewer methodology, Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines, and PICOTS (population, interventions, comparators, outcomes, timing, and setting) criteria identified 25 citations between 2001 and 2018; 18 were unique RCTs. Trial design characteristics, outcome definitions, assessment time points, and analyses populations varied across studies. Using "clinical response," an efficacy end point to health technology assessment agencies, we assessed potential network credibility, which collapsed from the overall data set to four studies and five interventions. This did not include closed loop(s) needed to assess consistency. Of the studies reporting clinical response, >70% of patients were ventilated at baseline with mean Acute Physiologic Assessment and Chronic Health Evaluation II scores from 14.7 to 17.5. Pseudomonas aeruginosa (range, 18.4-64.1%) and Klebsiella spp. (range, 1.6-49%) were the most common causative pathogens. We identified relevant RCTs for most standard-of-care agents approved for HABP/VABP, which provided a comprehensive evidence base. In summary, our appraisal of available evidence for the clinical response outcome among adult patients with HABP/VABP does not support the conduct of a scientifically robust and clinically meaningful NMA. Although this data is vital to registration, there are significant limitations in these trials for health technology assessments, payor decisions, guidelines, and protocol decisions.